PHRASEOLOGICAL UNITS IN IBRAYIM YUSUPOV’S POETRY - Sabirbaeva Guljayna Saparbay qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Phraseological units represent a stable and culturally significant layer of language that conveys figurative meaning rather than literal interpretation. In poetic discourse, such units function as semantic wholes and are understood through their contextual and oral meaning. This article investigates phraseological units, phraseological unities, and phraseological combinations in the poetry of the Karakalpak poet Ibrayim Yusupov. The aim of the study is to analyze their semantic and stylistic functions without altering the original poetic lines. The research is based on qualitative linguistic analysis, where phraseological expressions are interpreted according to their figurative meaning. The findings demonstrate that Yusupov’s poetry reflects national phraseological thinking and effectively combines traditional expressions with philosophical and modern concepts. This study contributes to the understanding of phraseology in Karakalpak poetic language within an international linguistic framework.